Halte a la repression! Liberte pour les prisonniers politiques au Pakistan Oriental! (Union Internationale des Étudiants)
Large red circle in reference to Bangladeshi flag; black splatter and text over it Poster advertising campaign for the release of political prisoners in East Pakistan PO-1517